(untitled) (TEST Ticontre. Theory Text Translation, 2023)
The essay compares the three Italian translations of the short novel Prokleta avlija (1954) by Ivo Andrić, considered a seminal work of late Serbian modernism. The versions by Jolanda Marchiori (1962), Franjo Trogrančić (1974), and Lionello Costantini (1992) are analyzed through a study of the meta-narrative passages and poetic comments of the authorial narrator to assess how the translators render their semantic stratifications. The intertwining of the literal and figurative sense, sometimes resolved in a single word (one of the most significant qualities of Andrić’s novel), is often difficult to single out. The frequent ambiguity of these expressions challenges the translators who, being aware of it, often cannot but choose either the literal or the metaphorical meaning and this consequently undermines the allegorical value achieved by Andrić’s text also through these very metanarrative ambiguities. Il saggio mette a confronto le tre traduzioni italiane del romanzo breve Prokleta avlija (1954) di Ivo Andrić, considerato l’opera più importante del tardo modernismo serbo. Le versioni di Jolanda Marchiori (1962), Franjo Trogrančić (1974) e Lionello Costantini (1992) sono analizzate prendendo in esame i passi metanarrativi e i commenti di poetica del narratore autoriale per verificare in che misura i traduttori siano riusciti a renderne le stratificazioni semantiche. L’intreccio tra il senso letterale e quello figurato, a volte risolto in un’unica parola (uno dei pregi più significativi del romanzo di Andrić), è spesso difficile da discernere. La frequente ambiguità di queste espressioni mette alla prova il traduttore che, quando le nota, è spesso costretto a scegliere tra il significato letterale e quello traslato, incrinando il valore allegorico che il testo di Andrić ottiene anche grazie alle ambiguità metanarrative.